Advances of Adsorption and Filtration Techniques in Separating Highly Viscous Crude Oil/Water Mixtures. Issue 16 (24th July 2021) - Yu, Jiacheng; Cao, Changqian; Pan, Yongxin
Abstract: The efficient separation of highly viscous crude oil/water mixtures caused by offshore crude oil exploitation, marine transportation, and oil recovery is still a big challenge. Adsorption and filtration techniques are considered as powerful and renewable approaches for oil/water separation because of their low cost and simple operation. However, conventional adsorption and filtration materials show poor separation performance due to the extremely high viscosity of crude oil. A variety of advanced adsorption and filtration materials have been developed very recently for the improvement of the crude oil/water separation performance, such as oil adsorption materials with in situ thermogenesis and filtration membranes with self‐cleaning property. In this review, the background of crude oil and crude oil/water mixtures are first described. Then, the fundamental wetting theories are also presented. Furthermore, the state‐of‐the‐art materials for viscous crude oil/water separation based on adsorption and filtration techniques are summarized respectively, including the separation mechanisms, strategies, fabrication methods, and separation performance. Finally, the conclusions and challenges for the viscous crude oil/water mixture separation are discussed. Abstract : Viscous crude oil/water mixtures cause damage to the ecosystem and need to be treated efficiently. The recent progress of viscous crude oil/water separation technologies based on advanced adsorption and filtration materials are summarized.